Short‐term hypoxic vasodilation in vivo is mediated by bioactive nitric oxide metabolites, rather than free nitric oxide derived from haemoglobin‐mediated nitrite reduction. (7th February 2014) - Umbrello, Michele; Dyson, Alex; Pinto, Bernardo Bollen; Fernandez, Bernadette O.; Simon, Verena; Feelisch, Martin; Singer, Mervyn
<x xml:space="preserve">Abstract</x> Key points Hypoxia increases blood flow through vasodilation, an adaptive response that increases oxygen availability to tissues. This response is probably mediated by nitric oxide (NO); different mechanisms have been postulated (increased de novo synthesis, release from preformed stores, reduced inactivation), but precise mechanisms remain controversial. In a short‐term rodent model, hypoxaemia was associated with hypotension and lower plasma nitrite levels suggestive of nitrite bioactivation; this was only partially reversed by NO synthase inhibition. Administration of sodium nitrite produced marked vasodilation and increased nitrosylation. Scavenging of NO had little effect. Early hypoxic vasodilation is mediated by a complex interaction of multiple NO‐related species, rather than by NO from haemoglobin‐mediated reduction of nitrite per se. NO and its metabolites play a pivotal role in the body's initial adaptation to an acute decrease in oxygen supply, probably offering protection against a supply–demand mismatch. Abstract Local increases in blood flow – 'hypoxic vasodilation' – confer cellular protection in the face of reduced oxygen delivery. The physiological relevance of this response is well established, yet ongoing controversy surrounds its underlying mechanisms. We sought to confirm that early hypoxic vasodilation is a nitric oxide (NO)‐mediated phenomenon and to study putative pathways for increased levels of NO, namely production from NO synthases, intravascular nitrite reduction, release from preformed stores and reduced deactivation by cytochrome c oxidase. Experiments were performed on spontaneously breathing, anaesthetized, male Wistar rats undergoing short‐term systemic hypoxaemia, who received pharmacological inhibitors and activators of the various NO pathways. Arterial blood pressure, cardiac output, tissue oxygen tension and the circulating pool of NO metabolites (oxidation, nitrosation and nitrosylation products) were measured in plasma and erythrocytes. Hypoxaemia caused a rapid and sustained vasodilation, which was only partially reversed by non‐selective NO synthase inhibition. This was associated with significantly lower plasma nitrite, and marginally elevated nitrate levels, suggestive of nitrite bioinactivation. Administration of sodium nitrite had little effect in normoxia, but produced significant vasodilation and increased nitrosylation during hypoxaemia that could not be reversed by NO scavenging. Methodological issues prevented assessment of the contribution, if any, of reduced deactivation of NO by cytochrome c oxidase. In conclusion, acute hypoxic vasodilation is an adaptive NO‐mediated response conferred through bioactive metabolites rather than free NO from haemoglobin‐mediated reduction of nitrite.